Self-directed arm-crank exercise to improve volitional control of the trunk in patients with subacute spinal cord injury: a multicentre, parallel-group, randomised controlled trial protocol - Tom E Nightingale; Joan L Duda; Shin-Yi Chiou; Eduardo Martinez-Valdes; Zubair Ahmed; Maria del Rocio Hidalgo Mas; Joshua Kearney; Vicki Middleton; Chuang-Yuan Chiu (BMJ Open)
Introduction A spinal cord injury (SCI) disrupts synaptic connections between the corticospinal tract and motor neurons, impairing muscle control below the injury site. Many individuals with an SCI have impaired trunk control, affecting the performance of activities of daily living and quality of life. Work has shown improvements in trunk control after home-based, unsupervised arm-crank exercise training (ACET) in people with chronic motor-incomplete SCI. However, no studies have examined ACET’s impact on trunk control in individuals with subacute SCI. This study aims to investigate ACET’s effects on trunk control in adults with subacute incomplete SCI, and its mechanisms, and its long-term benefits on neuropathic pain, psychological well-being, physical activity levels and health-related quality of life.Methods and analysis This multicentre, parallel-group, randomised controlled trial will evaluate self-directed ACET in 60 individuals with subacute SCI (<6 months postinjury). All participants will receive standard in-patient rehabilitation; the intervention group will additionally undertake a progressive ACET protocol for 8 weeks. Assessments will occur at baseline (T0), 4 weeks (T1), postintervention (T2) and 6-month follow-up (T3). Outcomes include static and dynamic sitting balance with kinematic measurements and high-density electromyography of the erector spinae, corticospinal excitability, muscle strength, functional independence and questionnaires of neuropathic pain, psychological well-being, self-efficacy and motivation, physical activity and health-related quality of life. Quantitative data will be analysed using mixed-model repeated measures ANOVAs and Student’s t-tests. Thematic analysis will be conducted on qualitative data obtained from focus groups in which the feasibility, enablers and challenges of ACET for individuals with subacute SCI will be discussed.Ethics and dissemination This study was approved by The Health Research Authority and Health and Care Research Wales (22/NS/0054). Results will be published in peer-reviewed journals. Findings will be presented at National and International conferences for researchers and clinicians. Finally, results will be disseminated to the SCI community.Trial registration number ISRCTN17247972